Late-line treatment in metastatic gastric cancer: today and tomorrow. (August 2019) - Smyth, Elizabeth C.; Moehler, Markus
Survival for patients with unresectable advanced or recurrent gastric cancer (GC) remains poor and the historical lack of evidence-based therapeutic options after second-line therapy is reflected in current clinical guidelines for this condition. Despite uncertainty about optimal therapeutic strategies, further treatment is appropriate for some patients after failure of second line and may prolong survival. This approach has been reported in clinical trials and is becoming more common in real-world clinical settings. Several prognostic factors may increase the likelihood that a patient will be eligible for treatment in the third-line setting, including geographic location, status at diagnosis and response to treatment. There has been little progress over the last decade until the results from two large phase III randomized controlled trials completed in the last year: the ATTRACTION-2 trial with the programmed cell death-1 (PD-1) inhibitor, nivolumab, in an Asian population; and the TAGS trial with the oral chemotherapy trifluridine/tipiracil in a global population. Both ATTRACTION-2 and TAGS reported positive results in third-line treatment in advanced GC in specific patient groups. A further recently reported study, KEYNOTE-059, which was a single-arm phase II trial of the PD-1 inhibitor pembrolizumab in a mainly non-Asian population, has provided evidence supporting the use of this immunotherapy in patients with advanced GC. As further third-line options become available, more GC patients are expected to benefit from an individualized evidence-based approach to later-line therapy, with a common goal of extending survival and improving outcomes for their refractory disease.